A novel fluorescence-based biosynthetic trafficking method provides pharmacologic evidence that PI4-kinase IIIα is important for protein trafficking from the endoplasmic reticulum to the plasma membrane - Bryant, Kirsten L (BMC Cell Biol, 2015)
BACKGROUND: Biosynthetic trafficking of receptors and other membrane-associated proteins from the endoplasmic reticulum (ER) to the plasma membrane (PM) underlies the capacity of these proteins to participate in crucial cellular roles. Phosphoinositides have been shown to mediate distinct biological functions in cells, and phosphatidylinositol 4-phosphate (PI4P), in particular, has emerged as a key regulator of biosynthetic trafficking. RESULTS: To investigate the source of PI4P that orchestrates trafficking events, we developed a novel flow cytometry based method to monitor biosynthetic trafficking of transiently transfected proteins. We demonstrated that our method can be used to assess the trafficking of both type-1 transmembrane and GPI-linked proteins, and that it can accurately monitor the pharmacological disruption of biosynthetic trafficking with brefeldin A, a well-documented inhibitor of early biosynthetic trafficking. Furthermore, utilizing our newly developed method, we applied pharmacological inhibition of different isoforms of PI 4-kinase to reveal a role for a distinct pool of PI4P, synthesized by PI4KIIIα, in ER-to-PM trafficking. CONCLUSIONS: Taken together, these findings provide evidence that a specific pool of PI4P plays a role in biosynthetic trafficking of two different classes of proteins from the ER to the Golgi complex. Furthermore, our simple, flow cytometry-based biosynthetic trafficking assay can be widely applied to the study of multiple classes of proteins and varied pharmacological and genetic perturbations.